Using strategic cost management to rationalize pricing decisions: applied research in Al Farouk General Contracting Company (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research aims at clarifying the concept of strategic cost management as it is a contemporary system that entered the field of scientific research and its importance in cost management As well as to identify the most important strategic cost management tools according to the classification of modern sources and the application of two tools to achieve the goal to achieve, this was to solve the problem suffered by Iraqi companies in general and contracting companies in particular the problem of rising costs of their products or services and the reason for the use of traditional systems in the calculation of costs These systems do not meet the requirements of the local or global market and the intense competition, which leads to a high price of the product or service and thus lose its market competition for its inefficiency in managing costs properly. The study concluded that the need to pay attention to research oriented towards the integration of cost management methods to serve the objectives of the company and applied to the company or the like, and also must seek to link strategic cost management tools with the company's strategic objectives to maximize the value of the company and enhance its competitiveness.